New Higher Education Model? Degree Apprenticeships as a Strategy to Modernize Apprenticeships: Rationale, Current Development in the U.S., and a Conceptual Framework - Jooyoung Voeller (International Journal for Research in Vocational Education and Training, 2023)
Purpose: To better prepare young people for the increasingly complex world of work in the global knowledge economy, apprenticeships are receiving renewed attention in countries without a strong history of vocational education. One of the strategies to promote and modernize apprenticeships in these countries is to offer apprenticeships integrated into degree programs, known as degree apprenticeships at the tertiary level. However, little research has been done to explore this new degree pathway. The purpose of this study is to explore the rationales and recent development of degree apprenticeships in the U.S. and to present a conceptual framework for designing and delivering such programs.